Optimization of LiFePO 4 synthesis by hydrothermal method - (:unkn) unknown (My University, 2014)
0

Optimization of the LiFePO 4 cathode active material synthesis process in the hydrothermal method consists of many factors, including pH, carbon coating, particle size optimization, sintering and hydrothermal synthesis temperature. The main goal of this study is to determine the effect of particle size, pH and carbon coating on capacity and cycle performance. In this study, LiFePO 4 cathode active materials were prepared at different pH (6.5 and 8.5) and temperature (160 and 180 ◦ C) levels using the hydrothermal method. The hydrothermal synthesis products were sintered at 400, 500, 600, and 700 ◦ C with 5% and 7% carbon source. The initial discharge capacity was observed as −1 130 mAh gfor the sample that was sintered at 700 ◦C. However, a 14% capacity loss was measured after 100 cycles. Additionally, the sample was ground for 10 h in a ball mill and sintered at 700 ◦C. The capacity was then increased to −1 151 mAh g -1 and the capacity loss was measured as 7% (140 mAh g−1) after 200 cycles.
Keywords: Mühendislik, Kimya